Sufism and Pandemic: Lesson Learned from Sufi Teachings and its Prominent Figures - Mohamad Nur Kholis Setiawan (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
Religious perspective is an important aspect to be used in dealing with the COVID-19 global pandemic and the Islamic one is not an exception. It is Sufism that concerns more on the spiritual dimension of Islam that might be taken into consideration. Based on several books on Sufi scholars and teachings, such as al-Isfahani’s Ḥilyat al-Auliyā’ wa-ṭabaqāt al-Aṣfiyā, al-Attar’s Tadhkirat al-Auliyā, al-Sakandari’s al-Ḥikam, and others, this article proposes Sufi teachings as inevitable tools in facing the pandemic. Using content analysis, intertextuality, and historical approaches, this paper concludes how Sufism with its basic teachings such as ‘uzlah, ṣumtu, qanā’ah, shukr,  et cetera, will be the suitable elements for Muslims to face and overcome the pandemic. Several prominent Sufi scholars will also be used to strengthen the argument.